2000
DOI: 10.1111/1467-9280.00291
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mathematical Reasoning Ability at Age 13: Their Status 20 Years Later

Abstract: Abstract-Reported

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
194
0
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(228 citation statements)
references
References 28 publications
(31 reference statements)
11
194
0
12
Order By: Relevance
“…Sex differences in eventual career choices for two cohorts of mathematically talented youth. Data are from Benbow, Lubinski, Shea,& Eftekhari-Sanjani (2000). Biopsychosocial model showing how genes, hormones, and experiences alter brain development and how individuals select experiences from the environment based on their predilections and past experiences, thus also altering the size and connectivity of their brains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in eventual career choices for two cohorts of mathematically talented youth. Data are from Benbow, Lubinski, Shea,& Eftekhari-Sanjani (2000). Biopsychosocial model showing how genes, hormones, and experiences alter brain development and how individuals select experiences from the environment based on their predilections and past experiences, thus also altering the size and connectivity of their brains.…”
Section: Resultsmentioning
confidence: 99%
“…Individuals who were assessed by age 13 as being in the top 1% in mathematical reasoning ability (cohorts 1 and 2) became highly educated: Over 90% earned a bachelor's degree, and over 25% earned a doctorate, with essentially no sex differences in degrees earned (Benbow, Lubinski, Shea, & Eftekhari-Sanjani, 2000). About 50% earned at least one postsecondary degree in math and science areas, with 64% of the top .5% in mathematical ability securing at least one postsecondary math or science degree (Benbow et al, 2000). The men were at least twice as likely to earn degrees in the inorganic sciences and engineering as the women, with the men earning almost five times as many doctorates in these areas as the women.…”
Section: Sex Differences In Career Development Choicesmentioning
confidence: 99%
“…Indeed, several studies have reported gender differences in math ability (e.g., Benbow, Lubinski, Shea, & Eftekhari-Sanjani, 2000;Hyde, Fennema, & Lamon, 1990;Mau & Lynn, 2000), showing that males outperformed females. Probably the strongest evidence for the existence of gender differences in mathematics performance comes from the Programme for International Student Assessment (PISA), published by the Organization for Economic Co-operation and Development (OECD, 2016), which assesses the competencies of 15-year-old students from 65 different countries in various subjects, including mathematics.…”
Section: Thinking and Reasoningmentioning
confidence: 99%
“…Despite consensus regarding, and concern for, this gender disparity in mathematically oriented careers even among mathematically gifted male and female students (Benbow, Lubinski, Shea, & Eftekhari-Sanjani, 2000), there is much controversy regarding the degree to which this disparity results from inherent vs. culturally influenced sex differences in math ability and performance. The research has been inconsistent in demonstrating whether ☆ A portion of this work was completed as a partial requirement for the first author's Master of Science in Engineering degree in the Department of Applied Mathematics and Statistics at Johns Hopkins University.…”
Section: Introductionmentioning
confidence: 99%